Appeal of rural tourism : a case study of Pulau Ubin. - Ho, Wen Dtin. (2009)
What is the appeal of rural areas? Why are there increasing numbers of people heading to the countryside? This research examines the reasons for the popularity of rural areas with a case study of Pulau Ubin, an offshore island hailed as the ‘last rural corner’ of urban Singapore. For the study, I proposed that people visits Pulau Ubin; not just to enjoy the physical natural landscape in the rural area but because Pulau Ubin embodies aspects of Singapore’s kampung past. I interviewed a total of 28 respondents and found out that the appeal of natural setting is a result of the high density urban living in Singapore. Another reason cited by the respondents for the appeal of the island are the kampongs still remaining there. The findings confirmed my initial hypothesis.